2021
DOI: 10.11609/jott.6122.13.2.17741-17752
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the butterfly (Lepidoptera) diversity of an urban landscape: Guwahati, Assam, India

Abstract: The paper deals with the butterfly diversity of Guwahati, Assam, India which was the result of a survey conducted from April 2016 to July 2020.  During the study period we recorded 249 species of butterflies belonging to six families namely Papilionidae (24 species), Pieridae (23 species), Lycaenidae (57 species), Riodinidae (two species), Nymphalidae (97 species), and Hesperiidae (46 species).  Twenty-eight species were recorded from commercial areas, 74 species from residential areas, and 248 species from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Nectar resources that include several ornamental plants such as Cosmos bipinnatus, Anthemis punctata, Dahlia pinnata, Tagetes erecta, Duranta repens, fruit crops such as Citrus spp., Psidium guajava, Prunus persica, Pyrus pashia and wild native plants such as Viburnum cotinifolium, Anaphalis contorta, Erigeron spp., Pyracantha crenulata, Berberis spp., Elaeagnus umbellata, Trifolium repens, Micromeria biflora, Salvia leucantha attracted many butterflies in the lush green hill garden and adjacent mixed forest. These results are similar to those studies reporting more butterflies in forest habitats compared to areas disturbed or altered by human activities (Bhardwaj et al, 2012;Arya et al, 2020a;Bohra and Purkayastha, 2021), while few studies have also reported the converse of this pattern (Chettri, 2015;Mukherjee and Mondal, 2020;Koirala et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Nectar resources that include several ornamental plants such as Cosmos bipinnatus, Anthemis punctata, Dahlia pinnata, Tagetes erecta, Duranta repens, fruit crops such as Citrus spp., Psidium guajava, Prunus persica, Pyrus pashia and wild native plants such as Viburnum cotinifolium, Anaphalis contorta, Erigeron spp., Pyracantha crenulata, Berberis spp., Elaeagnus umbellata, Trifolium repens, Micromeria biflora, Salvia leucantha attracted many butterflies in the lush green hill garden and adjacent mixed forest. These results are similar to those studies reporting more butterflies in forest habitats compared to areas disturbed or altered by human activities (Bhardwaj et al, 2012;Arya et al, 2020a;Bohra and Purkayastha, 2021), while few studies have also reported the converse of this pattern (Chettri, 2015;Mukherjee and Mondal, 2020;Koirala et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In second and third place, they were D. melanippus and P. sylvia, with individuals of 31 and 28, respectively. A presence of H. erylus in other places was previously reported by Bohra and Purkayastha (2021), who described that it was one of the species found among 249 species in the urban landscape of Guwahati, Assam, India. The authors described that it was considered a common species in the habitats of forested areas.…”
Section: The Diversity Of Butterfly Speciessupporting
confidence: 54%
“…e overall morphological structure of Fritillaria japonicum was described through data such as the length of branches at different levels, internode length of branches, and branch angle. Due to a large number of final branches (tertiary branches), they are usually built in batches by automatic generation in parametric modeling software, and then optimized and adjusted the crown shape of tree morphological structure according to field photos; e leaf density in the table ultimately determines the number of leaves in the three-dimensional tree model, and its numerical value is the ratio of the total number of leaves to the spatial volume of tree crown (the corresponding cylinder volume formed by crown width and crown height) [10,11].…”
Section: D Landscape Sense Creationmentioning
confidence: 99%